Pengaruh Parenting Styles dan Interaksi Dalam Peer Group Terhadap Karakter Pada Remaja - Virginiar Novanda; Rachmat Mulyono (‎‎‎TAZKIYA Journal of Psychology, 2015)
This study was conducted to discover whether parenting style and interaction in peer group have significant effect on teenagers' character. Demographic factors were also added, such as age and gender, whether these factors have significant effect on teenagers' character as well. Sample of this study is 210 teenagers in Ciputat area, Tangerang Selatan, age range of those respondents is 10 – 22 year old. Respondents were asked to complete all of the instrument which measure parenting styles, peer group interaction, and character. The result of this study indicates that there is significant effect of parenting style (authoritative), peer group interaction (openness and interaction frequency), age, and gender on teenagers' character.